How Foreign Students Learn ‘Bahasa Indonesia’ as a Second Language - Limantoro, Singgih Widodo (Universitas PGRI Adi Buana Surabaya, 2018)
Foreigners who learn 'Bahasa Indonesia' in Indonesia actually learn Indonesian as a Second Language in the real-world settings. They practice Indonesian in Indonesian-speaking culture so that they expect to improve their Indonesian proficiency in a conducive language environment. In this paper, the writer would like to investigate why and how the foreign students learn it at Ubaya Language Center in Surabaya, Indonesia for about one semester. As a matter of fact, a language is also a part of culture, therefore, when they learn the Indonesian cultural activities, they might also learn the Indonesian language through cultural exposure. Based on his overall survey findings, the participants or the foreign students learning Indonesian at ULC had some reasons, such as chance for working career, for travelling, and for improving the language competence. They also used the Indonesian skills in their daily lives. This conducive language environment, their motivation and strategies in learning Indonesian in Indonesia would also enhance the success of their language learning. Keywords: communicative competence, foster, how to learn, linguistic environment